Avian influenza H9N2 seroprevalence among swine farm residents in China. Issue 4 (4th January 2014) - Zhou, Pei; Zhu, Wanjun; Gu, Honglang; Fu, Xinliang; Wang, Lifang; Zheng, Yun; He, Shuyi; Ke, Changwen; Wang, Heng; Yuan, Ziguo; Ning, Zhangyong; Qi, Wenbao; et al.
<x xml:space="preserve">Abstract</x> In parts of southern China, some large‐scale swine farms are adjacent to lakes and ponds that are home to many types of birds. Some swine farms will also raise poultry for consumption and sale. Swine farms in rural China may be the source of the AIV outbreak. A seroepidemiological study was conducted among swine farm residents to understand the prevalence of antibodies against avian influenza virus (AIV) H9N2 in southern China. A total of 2, 006 swine farm residents were sampled. Serum samples were tested for the presence of antibodies against H9N2 AIV by hemagglutination inhibition (HI) and microneutralization assays. A total of 37 serum samples from swine farm residents were HI positive for A/chicken/Guangdong/V/2008(H9N2), and 24 serum samples (all of which were also HI positive) were microneutralization assays positive for A/chicken/Guangdong/V/2008(H9N2). Due to the special pig farming model in southern China, the residents are in close contact with different kinds of birds. Thus, controlling bird‐to‐human transmission of AIV in swine farms with poultry may be an important means of preventing widespread AIV infection in humans. J. Med. Virol. 86:597–600, 2014. © 2014 Wiley Periodicals, Inc.